Determinan Fungsi Kognitif pada Penderita Diabetes Melitus Tipe 2 - Nur Rahmah; Wa Ode Sri Asnaniar; Safruddin (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2026)
Diabetics have a 2-6 times higher risk of developing blood clots which is one of the causes of cognitive dysfunction which can occur due to increased blood sugar levels in the body which can cause various complications in the blood vessels including the central nervous system. The purpose of this study was to determine whether there is a relationship between age, gender, blood sugar levels, duration of DM and cognitive function in patients with Type 2 DM. The research design used was analytic observational with a crosssectional approach. The sampling technique in this study was perpusive sampling with a total sample of 53 respondents. This study uses pearson correlation statistical tests and chi square. This study uses cognitive function measurement using MMSE (Mini Mental State Examination) scores. Statistical results showed that there was a relationship between age and cognitive function in Type 2 DM sufferers with value (p = 0,001), there was no relationship between gender and cognitive function with value (p = 0.597), there was a relationship between blood sugar levels and cognitive function with value (p = 0,001), there is a long-standing relationship with DM with cognitive function with value (p = 0,001). The conclusion of this study is that there is a significant correlation between age, blood sugar levels, duration of DM and cognitive function in people with Type 2 DM and there is no relationship between gender and cognitive function. Further research is needed by increasing variables, samples and using other methods so that it can be used as comparison material and more accurate results.